Cold and dark captivity: Drivers of amphibian longevity. Issue 11 (31st August 2018) - Stark, Gavin; Meiri, Shai
Abstract: Aim: Longevity is a critical life‐history trait of organisms. Multiple abiotic and biotic factors are thought to exert different selection pressures, resulting in a great variation in species longevity. We examined factors that, according to evolutionary theories of senescence, are thought to be related to extrinsic and intrinsic mortality rates, and thus shape the variation in longevity among amphibians. Location: World‐wide. Time period: Present. Major taxa studied: Amphibia. Methods: We collected literature data on the maximum longevities of 527 amphibian species. Correcting for phylogeny and sample size, we modelled the relationship between amphibian longevity and body size. We also examined the effects of chemical protection, activity period, microhabitat preferences and annual temperature on amphibian longevity. Results: In general, members of larger amphibian species live longer. Body size, however, explained less of the variation in amphibian longevity than it does in mammals and birds. Nocturnal amphibians, species that use poison for defence and those inhabiting cold regions live longer, but microhabitat preferences had little effect. Main conclusions: Our results supported predictions of evolutionary theories of senescence. Large amphibians living in colder environments probably experience slower growth and metabolic rates, reducing intrinsic drivers of mortality and increasing longevity. Moreover, species that reduce extrinsic mortality pressures via chemical protection and nocturnality have increased longevity. Sampling captive animals and sampling more individuals of a species increases the chances of finding older individuals and should be corrected for when studying maximum longevity.